Regional times to equilibria and their impact on semi-quantification of [18F]AV-1451 uptake. Issue 11 (November 2019) - Heurling, Kerstin; Smith, Ruben; Strandberg, Olof T; Schain, Martin; Ohlsson, Tomas; Hansson, Oskar; Schöll, Michael
The semi-quantitative estimate standardised uptake value ratios (SUVR) correlate well with specific binding of the tracer expressed as distribution volume ratios (DVR) for the tau positron emission tomography tracer [ 18 F]AV-1451 uptake and are therefore widely used as proxy for tracer binding. With regard to tracer kinetic modelling, there exists a time point when SUVR deviates minimally from DVR, occurring when the specific binding reaches a transient equilibrium . Here, we have investigated whether the time to equilibrium affects the agreement between SUVR and DVR across different brain regions. We show that the time required to reach equilibrium differs across brain regions, resulting in region-specific biases. However, even though the 80–100 min post-injection time window did not show the smallest bias numerically, the disagreement between SUVR and DVR varied least between regions during this time. In conclusion, our findings suggest a regional component to the bias of SUVR related to the time to transient equilibrium of the specific binding. [ 18 F]AV-1451 uptake should consequently be interpreted with some caution when compared across brain regions using this method of quantification. The commonly used time window 80–100 min post-injection shows the most consistent bias across regions and is recommended for semi-quantification of [ 18 F]AV-1451.